COVID-19 IN SOUTH ASIA: HEALTH, ECONOMICS AND POLITICS - Basu, Deepankar; Srivastava, Priyanka (Investigación Económica, 2021)
This paper tracks the progression of, and the government’s response to, the COVID-19 pandemic in four South Asian countries —Bangladesh, India, Pakistan and Sri Lanka— between February 2020 and May 2021. We look at the daily reported COVID-19 cases and deaths per million population. The data shows clear patterns of two or more waves of the pandemic in South Asia. We consider COVID-19 testing, vaccination coverage, non-pharmaceutical interventions and the COVID-19 economic stimulus. Sri Lanka performs the best, Bangladesh has low reported cases and deaths, but that is perhaps because of low testing; Pakistan has the lowest vaccination coverage; India has been hit worst by the second wave and is doing mediocre in terms of testing and vaccination. In terms of the impact of the pandemic on lives lost, Sri Lanka is the best and India the worst performer. COVID-19 EN EL SUR DE ASIA: SALUD, ECONOMÍA Y POLÍTICA RESUMEN Este artículo estudia la respuesta del gobierno y su progresión ante la pandemia por el COVID-19 en cuatro países del sur de Asia —Bangladesh, India, Pakistán y Sri Lanka— entre febrero de 2020 y mayo de 2021. Reportamos las infecciones y muertes diarias por cada millón de habitantes relacionadas con el COVID-19. Los datos muestran patrones evidentes de dos o más oleadas de la pandemia. Consideramos las pruebas de COVID-19, la cobertura de vacunación, intervenciones no farmacéuticas y los estímulos económicos relacionados con la pandemia. Sri Lanka es el de mejor desempeño; Bangladesh tiene un menor número de casos y muertes reportados, pero quizá debido a su menor cantidad de pruebas; Pakistán tiene la menor cobertura de vacunación; India fue el país más afectado por la segunda ola y está exhibiendo un desempeño mediocre en términos de pruebas y vacunación. En cuanto al número de muertes, Sri Lanka es el de mejor desempeño y la India es el peor.